Polyvinyl Alcohol–Red Cabbage Nanofibers as pH-Responsive Freshness Sensors for Advanced Food Packaging Technology - Foliatini, Foliatini; Wibowo, Singgih; Rochaeni, Henny; Suhartini, Suhartini; Fachrurrazie, Fachrurrazie; Prianditya, Arzzaq Imanda; Hadriansyah, Pradnadia Putri; Siregar, Naura Athira Putri; Nurpadilah, Novi; Alfiani, Putri; Rahim, Maudi; Sriwahyuni, Endah (UI Scholars Hub, 2024)
The development of innovative food packaging technologies, particularly those capable of monitoring freshness, has become increasingly important in the food industry. This research explores the development of a pH-responsive freshness sensor using polyvinyl alcohol–red cabbage (PVA/RC) nanofibers. The nanofibers are fabricated through the electrospinning technique and meticulously analyzed via scanning electron microscopy, Fourier-transform infrared (FTIR) spectroscopy, and differential scanning calorimetry (DSC). The results underscore the fine structure of the nanofiber matrix, with an average diameter of 68 nm. FTIR analysis substantiates the presence of anthocyanin compounds from RC within the PVA/RC nanofibers, which confirms the integration of beneficial components into the nanofiber matrix. Moreover, DSC investigations reveal the outstanding thermal properties of PVA/RC, which demonstrates the resilience of the nanofibers to higher temperatures, with a melting point of 223 °C. Notably, the PVA/RC nanofibers with a 3:1 ratio exhibit excellent thermal stability, although the color change due to pH fluctuations shifts toward transparency. This study lays down the foundation for future exploration and the potential for a diverse array of applications and material enhancements. The findings presented herein open up new opportunities for the use of PVA/RC nanofibers in the development of freshness sensors, heralding a new era in smart food packaging technology.